Polyunsaturated Fatty Acid Intake and Symptom Severity of Patients with Schizophrenia in Ernaldi Bahar Hospital, South Sumatra, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Background/Aims: The treatment of schizophrenia is commonly viewed from a pharmacological and socialperspective, but issues of nutrient intake are seldom examined. However, the various study reported thatpolyunsaturated fatty acids (PUFAs) concentration is reduced in the plasma of schizophrenic. ThereforePUFAs intake may have a correlation with symptom severity of schizophrenic. This study aimed to assessthe PUFAs intake of schizophrenic and its correlation with symptom severity of of schizophrenic.Method: This cross-sectional study was conducted on 63 schizophrenia hospitalized patients in ErnaldiBahar Hospital, South Sumatra, Indonesia. The symptom severity of of schizophrenic were determinedusing the validated Indonesian version of PANSS. Dietary intake was assessed using a 3-day food weighing.Correlation between variables was determined using the Spearman Correlation Coefficient.Results: The result showed a significant negative correlation between omega-3 fatty acids and Positivescale, Negative Scale, General psychopathology and risk of aggression with r=-0.345, r= -0.408, r= -0.483,and r= -0.406 respectively (p
Keywords: Omega-3, omega-6, ratio of omega-6/omega-3, schizophrenia.